Unity 5.x game AI programming cookbook : build and customize a wide range of powerful Unity AI systems with over 70 hands-on recipes and techniques /: build and customize a wide range of powerful Unity AI systems with over 70 hands-on recipes and techniques. (2016) - Palacios, Jorge
No abstract available